Expectative Management of a Late-Diagnosis Twin Reversed Arterial Perfusion Sequences (TRAPS) - A Rare Case Report - Velika Devina; Herman Sumawan; Muhammad Alamsyah Aziz; Mohamad Fakih (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Twin Reversed Arterial Perfusion Sequence (TRAPS) is a rare and severe complication unique to monochorionic twin pregnancies, characterized by retrograde perfusion of a nonviable acardiac twin by a structurally normal pump twin. Management of TRAPS diagnosed in late gestation remains controversial due to limited interventional options and an unpredictable clinical course. While early fetal intervention is generally recommended, evidence supporting expectant management in late-diagnosed cases, particularly in resource-limited settings, remains scarce. We report a 31-year-old gravida 2, para 1 woman with a monochorionic diamniotic twin pregnancy complicated by TRAPS, who was referred to a maternal–fetal medicine clinic at 29–30 weeks of gestation. Given stable pump twin hemodynamics, late gestational age, and unavailability of fetal therapy, expectant management with intensive ultrasound surveillance was pursued. At 32 weeks, signs of evolving cardiac compromise prompted delivery by cesarean section. The pump twin survived with prematurity-related complications and was discharged in stable condition. This case highlights that expectant management may be a reasonable option in carefully selected late-diagnosed TRAPS cases when fetal therapy is unavailable, provided that close surveillance and timely delivery are ensured.